Submandibular gland pleomorphic adenoma: Histopathological capsular characteristics and correlation with the surgical outcome - Mantsopoulos, Konstantinos; Goncalvesa, Miguel; Koch, Michael; Iro, Heinrich; Agaimy, Abbas (Annals of Diagnostic Pathology, 2018)
Pleomorphic adenoma (PA) of the submandibular gland is known to have a very low recurrence rate. The aim of this study was to investigate the histopathological and capsular characteristics of submandibular gland PA, looking for any differences between submandibular PA and the reported data for PA of the parotid gland as possible explanation for its low recurrence rate. We reviewed 72 submandibular gland PM resected at our center between 2000 and 2016. Patient age ranged from 14 to 77 years (mean, 47.2). At least follow (range, 12 to 170 months; mean, 82), none of the 72 patients developed a local recurrence. Histologically, all of the tumors were encased by a complete and intact anatomical capsule (100%). Pseudopodia were detected in 11 (15.3%) and satellite nodules in 3 (4.2%) cases. The histological subtype (according to Seifert et al.) was classic (mixed) in 39 (54.2%), stroma-rich/myxoid in 18/72 (25%) and cellular in 15 (20.8%) cases. A complete rim of healthy pericapsular tissue encasing the tumor and its capsule was observed in only 23/72 (31.9%) cases. In conclusion, submandibular PAs are characterized by consistent presence of an intact anatomical capsule, infrequent occurrence of pseudopodia, a remarkably infrequent occurrence lower frequency of secondary satellite tumor nodules and a comparatively lower proportion of the fragile risky myxoid subtype. Despite the fact that surgery of the submandibular gland can frequently lead to focal capsular exposure, the aforementioned capsular characteristics of submandibular gland PA are probably responsible for the excellent oncologic results.
EVALuna2:34875